1996
DOI: 10.1115/1.2831303
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Analysis of Two-Dimensional Contact Problems

Abstract: Contact problems can be converted into the spatial frequency domain using Fast Fourier Transform (FFT) techniques. Spectral analysis is used to develop an algebraic relationship between the surface displacement and the contact pressure. This relationship can be used to find the contact pressure or displacement for the contact of smooth surfaces or the complete contact of rough surfaces. In addition to providing rapid, robust solutions to contact problems, the algebraic relationship contains details of the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(49 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…Björklund and Andersson (Andersson & S. Björklund, 1994) extended the conventional matrix inversion approach by incorporating friction induced deformations. Alternative techniques that aim to solve the elastic contact of rough surfaces are the Fast Fourier Transform (FFT)-based method introduced by Ju and Farris (Ju & Farris, 1996) and a follow-up extension, based on a varia-tional principle (Kalker, 1977), proposed by Stanley and Kato (Stanley & Kato, 1997). The contact between solids with realistic surface topographies under relatively small loads usually leads to plastic deformations.…”
Section: Introductionmentioning
confidence: 99%
“…Björklund and Andersson (Andersson & S. Björklund, 1994) extended the conventional matrix inversion approach by incorporating friction induced deformations. Alternative techniques that aim to solve the elastic contact of rough surfaces are the Fast Fourier Transform (FFT)-based method introduced by Ju and Farris (Ju & Farris, 1996) and a follow-up extension, based on a varia-tional principle (Kalker, 1977), proposed by Stanley and Kato (Stanley & Kato, 1997). The contact between solids with realistic surface topographies under relatively small loads usually leads to plastic deformations.…”
Section: Introductionmentioning
confidence: 99%
“…The radii of curvature and peak density in a surface profile are dependent on the sampling interval of the scanning instrument [21]. As the sampling interval for a given instrument decreases, more details of the surface are captured.…”
Section: Surface Topography Analysismentioning
confidence: 99%
“…Thomas [7] showed that these properties are not unique for a given surface, but change with the sampling rate of the instrument used to characterize the surface. Ju and Farris [8] also demonstrated the dependence of RMS curvature and slope on the sampling frequency. They showed that the RMS curvature can vary by more than three orders of magnitude and the RMS slope can vary by almost two orders of magnitude while the RMS height stays essentially constant as the sampling interval goes from 0.1 to 0.0001 mm.…”
Section: Intrinsic Surface Characterizationmentioning
confidence: 99%